Penerapan Pendekatan Sistem Pembelajaran dalam Organisasi Pendidikan Islam - Khabib, M Aliful; Risdiyanto, Heri; Rambas, Jaya Dwi; Romlah, Romlah; Arifin, Zainal; Rohman, Syaifur (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
This study aims to describe the implementation of a system approach in Islamic educational organizations. The research is qualitative in nature, employing a literature review methodology to address identified gaps in integrating Islamic values into educational practices. Previous research has often overlooked the comprehensive alignment between curriculum, educators, and technology in Islamic education. This study addresses this gap by analyzing primary sources and other relevant literature to understand how a system approach can harmonize these components. Data collection involved critical analysis of written documents and content analysis techniques to derive meaningful insights. Findings reveal that the system approach in Islamic education provides a robust framework for embedding Islamic values across all educational aspects. By integrating Islamic principles into the curriculum, balancing worldly and spiritual knowledge through tawhid, and implementing character development programs, the approach seeks to cultivate learners who excel both intellectually and morally. The results indicate significant potential for improving educational outcomes, including increased coherence between educational components and the enhancement of moral and ethical standards among students. Practical implications emphasize the need for adequate training for educators, investment in technological infrastructure, and policy support to overcome barriers like resource limitations and resistance to change. In conclusion, this study contributes to the understanding of systemic methods in Islamic education, offering actionable insights for policymakers and educators to foster an environment where Islamic values and modern educational demands coexist seamlessly. The findings highlight the approach’s role in shaping individuals who are well-prepared to navigate contemporary challenges while upholding Islamic ethics and principles.